On geodesic strongly E-convex sets and geodesic strongly E-convex functions - Kilicman, Adem; Saleh, Wedad (SpringerOpen, 2015)
In this article, geodesic E-convex sets and geodesic E-convex functions on a Riemannian manifold are extended to the so-called geodesic strongly E-convex sets and geodesic strongly E-convex functions. Some properties of geodesic strongly E-convex sets are also discussed. The results obtained in this article may inspire future research in convex analysis and related optimization fields.